2014
DOI: 10.5038/1911-9933.8.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Documenting Mass Rape: Medical Evidence Collection Techniques as Humanitarian Technology

Abstract: Abstract.Aim: Emerging global networks of human rights activists, doctors, and nurses have advocated for increased collection of medical evidence in conflict-affected countries to corroborate allegations of sexual violence and facilitate prosecution in international and domestic courts. Such initiatives are part of broader shifts in human rights advocacy to document human rights violations using rigorous, standardized methodologies. In this paper, I consider three principal forms of medical evidence to documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Sociologists have observed that material objects can accrue moral and economic worth affecting how actors make decisions about the value of their health, possessions, finances, and the natural environment (Barnard 2016;Degenshein 2017;Fourcade 2011;Livne 2014;Zelizer 2010). "Humanitarian technologies" define, standardize, and commensurate what counts as sexual violence (Morse 2014), and end-of-life palliative care moralizes scarcity of material medical interventions (Livne 2014). These examples reveal the entanglements of technologies with moral projects, yet sociologists of science, technology, and knowledge have yet to analyze how and why expert actors imbue technologies with symbolic value to justify that a certain technology is "the right tool for the job.…”
Section: Opioids and The Biomedicalization Of Sufferingmentioning
confidence: 99%
“…Sociologists have observed that material objects can accrue moral and economic worth affecting how actors make decisions about the value of their health, possessions, finances, and the natural environment (Barnard 2016;Degenshein 2017;Fourcade 2011;Livne 2014;Zelizer 2010). "Humanitarian technologies" define, standardize, and commensurate what counts as sexual violence (Morse 2014), and end-of-life palliative care moralizes scarcity of material medical interventions (Livne 2014). These examples reveal the entanglements of technologies with moral projects, yet sociologists of science, technology, and knowledge have yet to analyze how and why expert actors imbue technologies with symbolic value to justify that a certain technology is "the right tool for the job.…”
Section: Opioids and The Biomedicalization Of Sufferingmentioning
confidence: 99%
“…The process of documenting forensic evidence of sexual violence is ideally standardized using forensic medical certificates, which are formal documents–sometimes issued by a government or court system—that trained clinicians use to systematically record forensic medical evidence for use in legal proceedings [ 19 , 20 ]. An evaluation conducted in Kenya found that a greater degree of medical evidence documented using the Post-Rape Care (PRC) form (Appendix 1)—the standardized medical certificate used in Kenya–was associated with an increased likelihood of an adjudication outcome favoring the survivor [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as the book describes, most sexual assault cases do not proceed to trial, and available studies on case outcomes suggest no measureable correlation between forensic evidence and increased prosecution rates (Du Mont and White, 2007). These types of exams have been adopted by the World Health Organization and adapted for use in refugee camps and settings of armed conflict to document violations of international law and facilitate prosecution in domestic and international courts (Morse, 2014). Mulla’s analysis of the impact of these exams on victims in a relatively high-resource setting suggests great caution and, in her words, calls upon all concerned “to begin to imagine a way to challenge existing models and introduce more ethically informed modalities of intervention that better serve the needs of victims, nurses, prosecutors, rape crisis advocates, and even the state” (p. 36).…”
mentioning
confidence: 99%